The Use of E-Module Learning Media and Nursing Students’ Self Efficacy - Rahmawati, Fitri Eka; Susanti, Raini Diah; Mambang Sari, Citra Windani (Journal of Nursing Care, 2024)
There is a need for learning media innovation for students with pandemic conditions. The e-module learning media is part of the VnursLab 3D Simulator, consisting of 22 E-Modules and 3 E-Modules tested for effectiveness on student knowledge, satisfaction, and learning motivation. In this learning, media has a relationship with students' academic self-efficacy to achieve goals and overcome obstacles during learning. Purpose: Identifying an overview of the use of e-module learning media for Nursing students' self-efficacy. Method: This study uses a quantitative descriptive method with a cross-sectional approach using The College Academic Self Efficacy Scale (CASES) instrument, which has been carried out validation tests produced α>0.3 and a reliability of 0.931. This study used an e-module insertion catheter (Benign Prostatic Hyperplasia). The population of this study is active undergraduate nursing students level III at Padjadjaran University with purposive sampling totalling 110 students. Results: The results showed that the use of e-module learning media was dominated by self-efficacy results with a high category rather than a moderate category in nursing students. Conclusion: This concludes that respondent characteristics positively affect nursing students' self-efficacy, resulting in satisfactory academic achievement.